Review of Empoasca (Okubasca) Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini), first record from China and description of two new species - Liu, Yang; Qin, Dao-Zheng; Fletcher, Murray J.; Zhang, Ya-Lin (Zootaxa, 2011)
The subgenus Okubasca Dworakowska of the genus Empoasca Walsh (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini) is recorded for the first time from China, and revised with two new species described and illustrated from southern China: E. (O.) dianella Qin & Zhang sp. nov., E. (O.) calvata Qin & Liu sp. nov. Habitus photos and illustrations of male genitalia of these new species are given. A key to males of all three species of the subgenus is also provided.